2009
DOI: 10.1128/jb.01665-08
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxins in Redox Maintenance and Survival during Oxidative Stress ofBacteroides fragilis

Abstract: The anaerobe Bacteroides fragilis is a gram-negative, opportunistic pathogen that is highly aerotolerant and can persist in aerobic environments for extended periods. In this study, the six B. fragilis thioredoxins (Trxs) were investigated to determine their role during oxidative stress. Phylogenetic analyses of Trx protein sequences indicated that four of the six Trxs (TrxA, TrxC, TrxD, and TrxF) belong to the M-type Trx class but were associated with two different M-type lineages. TrxE and TrxG were most clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 54 publications
4
51
0
Order By: Relevance
“…MK1 at all sites (Figure 6), suggests that ferredoxin is not the main enzyme responsible for iron homeostasis in this organism. The very similar expression levels of genes coding for GRX and TRX in both microbial populations at all sites is not surprising, as the TRX/GRX multidomain protein is an ubiquitous thiol redox system in nature (Pedone et al, 2004;Reott et al, 2009). This is the first study to report on the concentrations of H 2 O 2 in acidic geothermal springs of YNP, and only one study has reported on peroxide levels in other high-temperature systems (Wilson et al, 2000a,b).…”
Section: Discussionmentioning
confidence: 86%
“…MK1 at all sites (Figure 6), suggests that ferredoxin is not the main enzyme responsible for iron homeostasis in this organism. The very similar expression levels of genes coding for GRX and TRX in both microbial populations at all sites is not surprising, as the TRX/GRX multidomain protein is an ubiquitous thiol redox system in nature (Pedone et al, 2004;Reott et al, 2009). This is the first study to report on the concentrations of H 2 O 2 in acidic geothermal springs of YNP, and only one study has reported on peroxide levels in other high-temperature systems (Wilson et al, 2000a,b).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly as in many non-pathogenic organisms' genomes, also in pathogens have been identified a number of Trx and TrxR. For example, Trx system is a major thiol-disulfide redox system in gram-negative, opportunistic pathogen B. fragilis (Rocha et al 2007) and contains six genes encoding homologues of Trx and one gene for TrxR (Reott et al 2009). Recently studies revealed that not all Trx proteins are still active and providing an active protection.…”
Section: Thioredoxin System Of Selected Pathogens As a Therapeutic Tamentioning
confidence: 99%
“…For example, the isolation of the putative Trx targets via Trxaffinity chromatography and the results from activation assays with select purified and deactivated enzymes have established that in Chlorobaculum tepidum, a green sulfur bacterium and an anaerobic phototroph, the thioredoxin system implements post-translational control on the tricarboxylic acid or the TCA cycle and sulfur metabolism and assists in the defense against oxidative stress (7). An analysis of mutant phenotypes and a gene expression study have revealed the critical roles of Trxs and TrxRs in the redox homeostasis and survival during oxidative stress in Bacteroides fragilis and Desulfovibrio vulgaris Hildenborough, respectively (6,14). Work with Clostridium pasteurianum, an anaerobic fermentative bacterium, has revealed a ferredoxin-dependent flavin containing TrxR (8).…”
mentioning
confidence: 99%
“…However, it has also been investigated significantly in the anaerobic organisms (6 -24) focusing on both the characteristics of the Trxs and TrxRs (6,8,9,(11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22)(23) and their physiological roles (6,7,10,14,20). For example, the isolation of the putative Trx targets via Trxaffinity chromatography and the results from activation assays with select purified and deactivated enzymes have established that in Chlorobaculum tepidum, a green sulfur bacterium and an anaerobic phototroph, the thioredoxin system implements post-translational control on the tricarboxylic acid or the TCA cycle and sulfur metabolism and assists in the defense against oxidative stress (7).…”
mentioning
confidence: 99%